2023
DOI: 10.1111/tops.12652
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Landscapes Through Language: The Role of Native Language and Expertise in the Representation of Waterbody Related Terms

Abstract: Landscapes are essential to human life: they provide a multitude of material (food, water, pollination) and nonmaterial (beauty, tranquility, recreation) values. Their importance is enshrined in international conventions and treaties, committing signatories to protecting, monitoring, and managing all landscapes. Yet, relatively little is known about how people conceptualize “landscape” and its constituents. There is emerging evidence that conceptualizations of landscape entities may influence landscape managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…They found significant differences between the tasks but no substantial effect of expertise. A recent study by Purves et al (2023) also failed to see such an effect. The authors compared the conceptualization of German and English-speaking experts and non-experts in geography on knowledge of 25 concepts related to water bodies (e.g., sea, river, reef ) by collecting sensory, motor, and affective ratings.…”
Section: Further Factors Affecting the Variability Of Geo Conceptsmentioning
confidence: 86%
See 3 more Smart Citations
“…They found significant differences between the tasks but no substantial effect of expertise. A recent study by Purves et al (2023) also failed to see such an effect. The authors compared the conceptualization of German and English-speaking experts and non-experts in geography on knowledge of 25 concepts related to water bodies (e.g., sea, river, reef ) by collecting sensory, motor, and affective ratings.…”
Section: Further Factors Affecting the Variability Of Geo Conceptsmentioning
confidence: 86%
“…Indeed, numerous pieces of evidence showed that geo categories consistently vary across contexts, cultures, and languages (e.g., Burenhult and Levinson, 2008 ; Turk and Stea, 2014 ) and are even more variable than other semantic domains (e.g., Battig and Montague, 1969 ; van Overschelde et al, 2004 ; van Putten et al, 2020 ). Importantly, geo-meaning is also influenced by many other potential factors, such as people’s level of expertise (e.g., Giannakopoulou et al, 2013 ; Purves et al, 2023 ; but see also Wartmann et al, 2014 ), the kind of implemented task (e.g., Mark et al, 1999 , 2001 ; Smith and Mark, 2001a , b ; Pires, 2005 ), living environments along with their perceived familiarity (e.g., Williams et al, 2012 ; Wartmann et al, 2015 ). So, our review indicates that geo concepts are a highly flexible class of words.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…J. Kim et al, 2023;Malt & Majid, 2023). Interestingly, scholarship has increasingly demonstrated that metaphors and language-and their heterogeneous affective qualities-are profoundly shaping children's learning and their capacities to value and act in ways that are important for socio-ecological systems (e.g., Malt & Marsh, 2023;Purves et al, 2023).…”
Section: Affect Awe and Emotionmentioning
confidence: 99%